Clinical Perspective of Antimicrobial Drugs in Pediatric Dentistry- An Update - Dhirja Goel; Seema Chaudhary; Naveen Manuja; Gaurav Kumar Goel (Wolters Kluwer Medknow Publications, 2024)
This review highlights the importance of judicious antibiotic prescribing practices for orofacial infections in pediatric patients. It emphasizes the need to adhere strictly to guidelines to mitigate the rising threat of antibiotic resistance. Antibiotics, alongside analgesics, are commonly prescribed by dentists due to their efficacy in treating infections. However, a significant portion of antibiotic prescriptions are unnecessary, contributing to the development of microbial resistance. Research indicates a concerning trend of low adherence to professional clinical guidelines among dental students, dentists, and pediatric dentists regarding antibiotic prescriptions. Despite the historical success of antibiotics in dental treatments, their overuse poses a risk to this achievement. Therefore, it's crucial to limit antibiotic use to reduce the risk of resistance development. Insufficient knowledge about significant clinical indications for antibiotic prescriptions among pediatric dentists exacerbates the problem, leading to overuse and contributing to antibiotic resistance in children. Addressing this knowledge gap and promoting adherence to guidelines is essential in preserving the effectiveness of antibiotics in pediatric dental care.